Perkelahian Kuda pada Masyarakat Muna - Akhmad Marhadi; Syawal . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
This study aimed to determine and describe the process and meaning of horse fight in Muna Society Labasa Rural, District of South Tongkuno Muna. Data collected through observation and interviews. The results indicated that horse fight was a Muna cultural richness. This tradition was still been held and would be continued as inherited to the next generation. Horse fight took place with some stages, they were: (1) conducting meetings, (2) preparation of the handler and the horse, herding horses into the arena, (3) fight for horses, and (4) the end of horse fight. As for the meaning contained in horse fight was that self-esteem should be maintained, taught the faithful nature, taught us about how to beat the opponent, taught us to always be vigilant, and unite the Muna society. Key words: horse fight, South Tongkuno, Muna culture